(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
Materials and methods: herbarium collections, literature data, field observations. Nomenclature: POWO 2023. Results: On current estimations, family of Caryophyllaceae counts about 90 genera and from 2200 to 3000 species widespread on all continents, but mainly out of tropics. For the flora of Ukraine 49 genera (three from them need confirmation) and 231 species (with subspecies) have been reported. Most numerous native species are genera Dianthus – 49 species (with sub-species), Cerastium – 23, Otites – 17, Silene – 17 (with subspecies), Gypsophila – 11, Minuartia s. str. – 8, and other. At the same time many genera are presented by one or two species (Agrostemma, Bufonia, Carpophora, Cucubalus, Elisanthe, Heliosperma, Kohlrauschia, Lychnis, Myosoton, Paronychia, Pleconax etc. As compared to previous edition of cheklist, changes in specific composition of many genera: Dianthus, Silene, Elisanthe, Minuartia, Stellaria took place, new genera have been distin-guished in many of them: from the genus Stellaria – Alsine, Hylebia, Rabelera; from Silene – Atocion; from Elisanthe – Carpophora, Silenanthe; from Minuartia – Cherleria, Sabulina. Significant nomenclatural changes were made to the genus and species names and taxonomic status of many species. Many species that were previously reported for Ukraine need con-firmation (they are reported only based on literature data, old collections, or based on only one herbarium specimen): Dianthus corymbosus, D. giganteiformis, D. pinifolius, D. pontederae, D. seguieri, D. serotinus, D. spiculifolius, Eudianthe coeli-rosa, Pseudosaponaria pilosa (≡ Gypsophila pilosa), Kohlrauschia velutina, Melandrium astrachanicum, M. nemorale, Moehringia lateriflora, Polyschemone nivalis (≡ Silene nivalis), Sagina apetala, S. hawaiensis (= S. subulata), Silene thymifolia, Spergularia syvaschica, Viscaria alpina. The Central European species Dianthus grationopolitanus (= Dianthus caesius), which has disappeared from the flora of Ukraine, was previously mentioned in all floristic records for the vicinity of Zalishchyka (Khreshchatyk village, Zastavniv district, Chernivtsi region). The extinct species is Heliosperma arcanum (≡ Ixoca arcana), described by H. Zapalovich from the vicinity of the town of Zalishchyka (Ternopil region), according to the collections of G. Zipser, no one else found after 1855.